Factors influencing oocyte yield and embryo quality in donor IVF cycles: a retrospective cohort study - Lin, Pin-Yao; Lee, Chun-I; Chen, Hsiu-Hui; Huang, Chun-Chia; Chen, Ming-Jer; Yu, Tzu-Ning; Lee, Tsung-Hsien; Lee, Maw-Sheng (Frontiers in Endocrinology, 2025)
BackgroundAchieving an optimal balance between oocyte yield and embryo quality is central to donor IVF. Although anti-Müllerian hormone (AMH) predicts oocyte quantity, donor characteristics and stimulation parameters may influence embryo developmental competence. We aimed to identify clinical and protocol-related factors associated with oocyte yield and embryo quality in a large donor cohort.MethodsWe retrospectively analyzed 584 donor IVF cycles at a single center (Jan 1, 2018–Dec 31, 2023). Donor variables included age, AMH, BMI (body mass index), and baseline hormones. Stimulation used gonadotropin-releasing hormone (GnRH) antagonist (27.1%) or progestin-primed ovarian stimulation (PPOS)(72.9%); recombinant human luteinizing hormone (LH) was used in 86% of cycles; final maturation was GnRH agonist (GnRHa) (59.4%) or dual trigger (40.6%). Outcomes were oocyte yield and embryo quality metrics (maturation, two-pronuclear (2PN) fertilization, Day 3 good-quality embryo rate, blastocyst formation rate, and top-quality blastocyst rate). Multivariable linear regression and propensity score matching (PSM) compared protocols and LH supplementation.ResultsDonors were 25.6 ± 3.7 years with AMH 6.1 ± 2.9 ng/mL and BMI 21.6 ± 2.8 kg/m². Per cycle: 27.1 ± 11.1 oocytes, 20.8 ± 8.3 MII (maturation 78.2 ± 13.4%), 2PN fertilization 73 ± 18%, Day 3 good-quality embryos 10.6 ± 6.0 (69.5 ± 23.5%), blastocysts 9.5 ± 5.5 (56.7 ± 22.5%), and top-quality blastocysts 6.1 ± 4.2 (36.5 ± 20.1%). First transfers (n=491) yielded 55.4% clinical pregnancy and 44.4% live birth; miscarriage 12.2%. AMH independently predicted oocyte number; higher BMI was associated with lower fertilization. PPOS produced lower Day 3 good-quality embryo (67.9% vs 72.8%) and top-quality blastocyst rates (59.7% vs 74.1%) versus antagonist in PSM, with similar blastocyst formation rate (64.0% vs 60.9%). LH supplementation modestly increased fertilization (74.4% vs 69.5%) without downstream differences. Dual trigger was associated with reduced blastocyst formation rate but a higher proportion of top-quality blastocysts.ConclusionsIn donor IVF, AMH is the principal predictor of oocyte yield, whereas BMI, stimulation protocol, and trigger method influence embryo quality. Despite protocol-dependent morphology differences, pregnancy and live birth rates remained high. Findings support individualized stimulation strategies that consider donor profile and protocol effects to optimize efficiency and outcomes.